Household’s Fuel Type Choice for Space Heating in Türkiye: A Comparison of Multinomial Logit and Multinomial Probit Models - Çelik, Ali Kemal; Tamer, Betül (International Journal of Energy Economics and Policy, 2024)
Better understanding of households’ fuel type choice behaviour for residential heating, cooking, or lighting purposes would provide valuable information in estimating households’ energy use and in developing efficient fuel switching and energy saving policies; these solutions could include reducing consumption and utilising renewable energy sources. This paper aims to explore potential determinants of household’s fuel choice for residential heating in Türkiye. Using nineteenth wave of Household Budget Survey which was administered to 11,828 households and 40,688 individuals throughout the country, the data were analysed using both multinomial logit (MNL) and multinomial probit (MNP) models due to unordered nature of the dependent variable category. The empirical findings indicate household type, type of dwelling, residence time, the age of dwelling, the number of rooms, housing size, household size, type of floor structure of dwelling, household annual disposable income (log), household head’s occupation level, type of heating system, car ownership, and type of employment were found as statistically significant factors affecting Turkish household’s fuel choice for residential heating. Household annual disposable income and type of heating system had the highest impact on household’s final fuel type decision. Results also reveal that MNL is more parsimonious model than MNP model.